Bladder cancer immunotherapy parallel advances in BCG optimization and next-generation vaccine platforms - Li, Fengshuo; Wang, Dawei; Gao, Yuan; Cui, Yuanshan (Frontiers in Immunology, 2025)
Bladder cancer (BCa) remains a significant global health challenge with rising incidence and suboptimal outcomes in advanced stages. Although immunotherapy for urological cancers is not a new treatment, recent clinical advances have confirmed the value of immunotherapy as a urological cancer treatment. In the field of cancer immunotherapy, increasing attention has been focused on the use of cancer vaccines that activate T cells to target growing tumors. Despite Bacillus Calmette-Guérin (BCG) intravesical immunotherapy serving as the first-line treatment for non-muscle-invasive bladder cancer (NMIBC), its limitations, including systemic toxicity, BCG unresponsiveness, and rapid bladder clearance-necessitate novel therapeutic strategies. This descriptive review synthesizes recent advances in BCG optimization and emerging cancer vaccines for BCa, including peptides, antigen-presenting cells, viruses, or nucleic acids, that seeks to stimulate the patient’s immune response targeting tumor cells. Our study underscores the transformative potential of next-generation vaccines in redefining BCa management while addressing critical barriers to implementation.